Impact of Delayed Recognition of Iatrogenic Ureteral Injury in a Retrospective Population-Based Study. Issue 6 (23rd November 2021) - Locke, Jennifer A.; Matta, Rano; Saskin, Refik; Nguyen, Francis; Neu, Sarah; Herschorn, Sender
Abstract: Introduction: Iatrogenic ureteral injuries (IUIs) are rare but can lead to significant consequences if unrecognized at the time of injury. We compare the impact of immediate vs delayed recognition of IUIs on clinical, cost and health care utilization outcomes. Methods: We conducted a population-based retrospective cohort study on patients who had a diagnosis of an IUI between 2003 and 2018. The primary independent variable was the time of diagnosis of IUI. The primary clinical outcomes evaluated included renal impairment and a composite outcome: hydronephrosis or stricture. Secondary outcomes included total direct health care costs and health care utilization. Results: We identified 1, 193 patients who experienced an IUI, 25.2% of whom had a delay in recognition. Delayed recognition of IUI was associated with hydronephrosis or stricture within 1 year following treatment of IUI (OR 2.27, 95% CI 1.69–3.04, p <0.0001) and renal impairment within 2 years following treatment of IUI (OR 2.69, 95% CI 1.84–3.94, p <0.0001) compared to immediate diagnosis. Total health care costs (incident rate ratio [IRR] 2.06, 95% CI 1.89–2.24, p <0.0001), emergency department visits (IRR 2.07, 95% CI 1.77–2.43, p <0.0001), hospitalizations (IRR 1.62, 95% CI 1.48–1.78, p <0.0001) and outpatient urology visits (IRR 1.45, 95% CI 1.31–1.60, p <0.0001) were significantly higher in those with delayed recognition compared to immediate. Previous radiation was significantly associated with delayed recognition of IUI (OR 0.64, 95% CI 0.42–0.97, p=0.04). Conclusions: Delayed recognition of IUI is associated with significant clinical, cost and health care utilization consequences.